PENERAPAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT PADA PELAJARAN SOSIOLOGI DI SMA MUJAHIDIN PONTIANAK - Wardani, Andita Wulan; Sulistyarini, Sulistyarini; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The title of this research is Analysis of the implementation of Cooperative Learning model of type Teams Games Tournament on Sociology subject of class XI IIS 3 Mujahidin Pontianak.Â theproblem in this research is how the application of Cooperative Learning model of type Teams Games Tournment on Sociology subject of class XI IIS 3 SMA Mujahidin Pontianak. The purpose of this study is the implementationÂ planning, impementation and evaluation after applying Cooperative model of type Teams Games Tournment on Sociology subject of class XI IIS 3 SMA Mujahidin Pontianak. This research approach is qualitative approach with descriptive method. Data collection techniques such as observation, techniques, interview guides and documentation. Based on the observations, the application of the TGT model has five steps : class presentation, group division, game and award for the group that get the highest score. In thi research, the teacher carries out all stages of the TGT model in Sociology Learning.Â Keyword : Model Of Learning Teams Games Tournament, Sociology.